Analytical Study of Physical Fitness Components for Football Juniors in Some Clubs in DhiQar Governorate - Ali Hussein Ali Al-Saeedi (Sinar Sport Journal, 2025)
Purpose of physically training adolescents in sports clubs is to get them ready for physical and technical effort by boosting their physical and psychological levels. Modern football is a game that takes a significant deal of physical effort and fitness, thus it has become vital to train youngsters physically throughout the preparation and formation stage, since this is the basic stage that prepares the player physically for matches and tournaments. Thus, the research problem is defined in "An Analytical Study of Physical Fitness Components for Football Juniors in Some Clubs in Dhi Qar Governorate" during the preparation process phase, the lack of a clear methodology or general vision for physical preparation programs and plans for football juniors in sports clubs, Particularly when they represent governmental institutions that specialize in training a big proportion of young people to contribute to the clarity of current information based on scientific principles and grounds that allow for greater development of physical capacities. This encouraged the researcher to identify current training material and its link to physical ability levels throughout the preparation phase